The prevalence of low back pain in cricketers – An undergraduate epidemiological study - Ian Harris (South African Journal of Physiotherapy, 1993)
The prevalence of Low Back Pain (LBP) in cricketer's was determined and possible causative factors were investigated. Questionnaires were sent to 110 cricketers playing for their first times of both clubs and schools during the 1991/92 season. The return response was 90% with a prevalence of LBP at 61.6%. Of these 78.7 % cited cricket as being the primary cause of their LBP. The injuries were predominantly grade 1 (72.1%), followed by grade 3 (23.1 %) and grade 2 (6.6%). Grading was made according to the effect the pain had on the cricketers game. Fast bowlers proved to be more at risk of developing LBP with a group prevalence of 75.6% followed by wicket keepers at 63.6%, batsmen at 56.8% and slow bowlers at 48.1%. Cricketers had rather a poor general knowledge of ways of protecting their backs. Recommendations were made to help reduce the high prevalence of LBP, especially amongst Fast bowlers and in cricketers in general.